Optimizing the Role of the Young Generation in Environmental Preservation as a Form of National Defense: Reflections on the 79th Independence of the Republic of Indonesia - Pambudi, Yonathan Suryo; Sudaryantiningsih, Cicik (Indonesian Journal of Advanced Research, 2024)
This article examines the strategic role of the younger generation in environmental preservation as a form of non-military national defense, with reference to the reflection of the 79th anniversary of Indonesia's Independence. This study uses literature reviews from various international sources indexed by Scopus and other reputable journals to explore the contribution of youth in environmental conservation and its relationship with national resilience. This article also discusses the methodology used in previous studies on youth and environmental conservation, as well as their impact on public policy. The method used is a literature review that focuses on the contribution of youth in environmental conservation programs and the use of green technology. The results of the study show that youth involvement is very important in strengthening national resilience, both through public policy, participation in conservation, and technological innovation. In addition, support from the private sector, NGOs, and the government is urgently needed to empower youth so that they can play an active role in strengthening national sovereignty and environmental sustainability. The research also highlights the great potential of the use of digital technology and social media to increase youth engagement in environmental movements and support the role of national defense.